Evaluating the outcomes of the Allan Gray Orbis Foundation's fellowship programme - Pokpas, Carlynn (Organisational Psychology, 2025)
Entrepreneurship plays a crucial role in economic development and job creation, particularly in South Africa, where youth unemployment remains a pressing issue. Entrepreneurship Education and Training (EET) interventions have proven effective in fostering entrepreneurial mindsets and competencies. This dissertation presents an outcomes evaluation of one such intervention: the Allan Gray Orbis Foundation's Fellowship Programme, which focuses on university students. Guided by Brinkerhoff's Success Case Method (SCM), the evaluation adopted a qualitative approach, drawing on interviews with 14 past Fellowship beneficiaries, including programme non-completers. The study aimed to assess whether the programme achieved its intended outcomes and identify the factors that either facilitated or hindered these outcomes. The findings suggest that the Fellowship has been effective in meeting its intended objectives, particularly in developing an entrepreneurial mindset – with strong support for key traits such as resilience, self-efficacy, and action orientation – and in stimulating entrepreneurial intention, with some participants progressing to venture creation. The integration of entrepreneurial role models and personal development support were identified as key drivers of the programme's positive outcomes. However, the evaluation highlights areas for improvement, such as enhancing mentorship and support structures, and increasing practical learning opportunities. Several recommendations are provided to address these gaps. This study contributes to the limited body of knowledge on programmes like the Fellowship, which was found to be relatively unique. It also provides valuable insights into the experiences of non-completers of entrepreneurship education interventions, a group that is seldom explored in similar assessments.